2018
DOI: 10.1186/s12890-018-0613-9
|View full text |Cite
|
Sign up to set email alerts
|

The relation between air pollution and respiratory deaths in Tehran, Iran- using generalized additive models

Abstract: BackgroundSome epidemiological evidence has shown a relation between ambient air pollution and adverse health outcomes. The aim of this study was to investigate the effect of air pollution on mortality from respiratory diseases in Tehran, Iran.MethodsIn this ecological study, air pollution data was inquired from the Tehran Province Environmental Protection Agency and the Tehran Air Quality Control Company. Meteorological data was collected from the Tehran Meteorology Organization and mortality data from the Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 27 publications
4
38
0
Order By: Relevance
“…Generalized additive models (GAM) were used to assess the associations of exposure to PM 2.5 and SWT with CVD mortality [30][31][32]. The regression models included the following components:…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Generalized additive models (GAM) were used to assess the associations of exposure to PM 2.5 and SWT with CVD mortality [30][31][32]. The regression models included the following components:…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Taghvaee et al [12] reported that diesel exhaust and industrial emissions have a greater impact on cancer risks (~70%) than other air pollution sources in Tehran. Tehran is not the city in Iran with the worst air pollution, however, it has received more attention [8,[12][13][14][15][16][17][18] because of its large population (estimated to be 9 million in 2019 [19]). Dehghan et al [18] investigated the impact of Tehran's air pollution on the mortality rate related to respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Tehran is not the city in Iran with the worst air pollution, however, it has received more attention [8,[12][13][14][15][16][17][18] because of its large population (estimated to be 9 million in 2019 [19]). Dehghan et al [18] investigated the impact of Tehran's air pollution on the mortality rate related to respiratory diseases. They reported that from 2005 to 2014, high concentrations of O 3 , NO 2 , PM 10 , and PM 2.5 were strongly associated with 46%, annual precipitation of 429 mm, and temperature range from −5 to 38 • C. Elevation in Tehran varies significantly from 1117 to 1712.6 m above sea level.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the known advantages of ecological studies as have been discussed extensively [45][46][47], the major advantage of our study is the application of CGAM in analysis. Generalized additive models (GAM) have been widely implemented in time-series studies to explore the relationship between environmental factors and health outcomes because they can control for seasonal trends and nonlinear modi cation effects of multiple variables, adding to the fact that they are more maneuverable than full-parameter alternatives, generalized linear models [48,49]. However, the traditional GAM only assumes the smoothness of the nonlinear associations and cannot restrict their shape.…”
Section: Discussionmentioning
confidence: 99%